Combined targeted DNA and RNA sequencing of advanced NSCLC in routine molecular diagnostics: analysis of the first 3000 Heidelberg cases - Volckmar, Anna-Lena; Leichsenring, Jonas; Kirchner, Martina; Christopoulos, Petros; Neumann, Olaf; Budczies, Jan; Oliveira, Cristiano; Rempel, Eugen; Buchhalter, Ivo; Brandt, Regine; Allgäuer, Michael; Talla, Suranand Babu; et al. (International journal of cancer, 2019)
Here, we demonstrate the feasibility and clinical utility of comprehensive, NGS-based genetic profiling for routine workup of advanced NSCLC based on the first 3000 patients analyzed in our department